Effect of honey supplementation on anaerobic performance / Harith Zaqwan Saifullizan - Saifullizan, Harith Zaqwan (Faculty of Sport Science and Recreation, 2019)
The purpose of this study was to investigate the effect of honey supplementation on anaerobic performance among recreational runners from Faculty of Sports Science and Recreation. A total of thirty subjects (N=30); (20.43±O.50) in years, height (l69.33±5.19) in centimeters and weight (64.37±8.44) in kilograms. Body mass index (22.41±2.53) in kg.m-2 were involved in this study and selected through purposive sampling method. The study is to investigate the effect of honey supplementation on anaerobic capacity. Paired Sample T-Test was used to analysed this study, the study includes pre-test and post-test by using all thirty sample. All subjects were selected by attend the selection and able to surpass the inclusion criteria needed. During pre-test, all subjects performed 30 seconds Wingate test. After the pre-test, all subjects must drink a honey drink that contains 20g of Kelulut Honey and 300ml of water and blood sample will be collected. All subjects must rest passively for 3 hours and everyone-hour blood pressure, heart rate and room temperature will be measured. For the post-test, all subjects performed the 30 seconds Wingate test and blood sample will be collected. Based on the Paired Sample T-Test results, there is no significant between pre-test and post-test (P = 0.553). The overall results also indicated the pre-test (l3.37±0.69) and post-test (l3.52±O.69). To conclude, this finding suggests honey supplementation does not had effect on anaerobic performance among recreational runner Faculty of Sports Science and Recreation.